2020
DOI: 10.4103/jips.jips_68_20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of flexural strength of Zirconia using three different connector designs: An in vitro study

Abstract: Aim: The aim of this study is to evaluate the flexural strength of zirconia using three different connector designs under vertical and oblique loads. Setting and Design: Invitro - analytical study. Materials and Methods: For simulating zirconia fixed partial prosthesis, a specimen with three octagonal cylinders connected with each other was designed. Each face of the octagon was 3.75 mm ± 0.1 mm, and the total width was 9 mm ± 0.1 mm with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Schmitter et al, in their prospective cohort study, evaluated the two-year clinical performance of extended tooth-supported zirconia, recommending 9 mm 2 as the minimum size for connectors in the cross-sections of the FDPs [61]. They also concluded that triangular connectors presented greater resistance to bending from vertical forces, while circular connectors presented better results against oblique loads [62]. Therefore, the importance of the connector design as a factor in the predictability of FDPs is clear [63].…”
Section: Discussionmentioning
confidence: 99%
“…Schmitter et al, in their prospective cohort study, evaluated the two-year clinical performance of extended tooth-supported zirconia, recommending 9 mm 2 as the minimum size for connectors in the cross-sections of the FDPs [61]. They also concluded that triangular connectors presented greater resistance to bending from vertical forces, while circular connectors presented better results against oblique loads [62]. Therefore, the importance of the connector design as a factor in the predictability of FDPs is clear [63].…”
Section: Discussionmentioning
confidence: 99%